2010
DOI: 10.4038/suslj.v7i1.1845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding velvet beans (<i>Mucuna pruriens</i>) on the lipid profile of broiler chickens

Abstract: The effect of feeding velvet bean (Mucuna pruriens) meal on the lipid profile in broilers was investigated. Two hundred, 14 days old broiler chicks were randomly allocated to five dietary treatments in a completely randomized design and feeding continued for four weeks. Maize and soybean meal based control feed and four test diets prepared from the control feed by incorporating velvet beans at 10, 15, 20 and 25% levels served as five dietary treatments. Feed intake was unaffected by velvet beans. Serum total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Average daily feed intake showed a linear decrease with increasing inclusion levels of MPSM. Our results are in agreement with (Carew et al, 2003;Jayaweera et al, 2007) who also reported a decline in average daily feed intake of broilers. Generally, heat processing results in detoxi cation of the anti-nutritional factors (ANFs), hence, enhancing protein absorption, bioavailability of the amino acids in the gut and higher palatability ; Tuleun and Igba, 2008; Gurumoorthi and Uma, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Average daily feed intake showed a linear decrease with increasing inclusion levels of MPSM. Our results are in agreement with (Carew et al, 2003;Jayaweera et al, 2007) who also reported a decline in average daily feed intake of broilers. Generally, heat processing results in detoxi cation of the anti-nutritional factors (ANFs), hence, enhancing protein absorption, bioavailability of the amino acids in the gut and higher palatability ; Tuleun and Igba, 2008; Gurumoorthi and Uma, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…To reduce the quantity of soybean meal used when formulating poultry diets, M. pruriens seeds can be used as a protein source and as a source of lysine which is one of the limiting amino acid that is usually supplemented in broiler diets (Jayaweera et al, 2007;Ani, 2008;Vadivel and Pugalenthi, 2010). However, its effect on meat quality has not been investigated, as it has been found that dietary ingredients affect meat quality (Mir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, consumption of MSM induces anabolic effects and increases muscle mass mediated through its ability to increase growth hormone (Alleman et al, 2011 ), testosterone (Suresh and Prakash, 2012 ), and dopamine (Lieu et al, 2012 ). Also, consumption of MSM has been demonstrated in poultry and rodent studies to induce hypoglycemic, lipid, and low-density lipoprotein cholesterol lowering effects (Jayaweera et al, 2007 ; Dharmarajan et al, 2012 ; Ngatchic et al, 2016 ). Further, MSM incorporation into beef diets has been shown to decrease meat cooking losses (Yantika et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%